The bronchial asthma: the use of exercises of Thai Chi in Baracoa - Emilio Lobaina-Torres; Lourdes Utria-Figueroa (Universidad de Guantánamo, 2016)
In the present work a current issue related to the need to enhance the treatment of bronchial asthma in asthmatic children through exercises of Tai Chi combined with the use of color therapy is addressed. The application of different research methods helped to confirm the shortcomings that hindered development in the treatment of bronchial asthma, various methods such as observation, surveys, interviews, etc. were applied, in order to determine the situation presented in the asthmatic children, actions which give teachers of Physical Culture Therapeutics varied and simple tools that are based on the main objectives of the current program and practical effectiveness of the exercises applied was corroborated by patients and families which gives validity to this paper to solve the problem posed.